Comparing the effects of microgravity and amyotrophic lateral sclerosis on mouse dorsal root ganglia - Yoshikawa, Masaaki; Matsukawa, Mutsumi; Oshima, Hideki; Ishikawa, Chihiro; Li, Haiyan; Kudo, Takashi; Shiba, Dai; Shirakawa, Masaki; Muratani, Masafumi; Takahashi, Satoru; Uemura, Mamoru; Aizawa, Shin; et al. (Frontiers in Space Technologies, 2023)
Microgravity (MG) exposure causes motor deficits and decreased neuronal activity, effects that resemble the ones observed in motor neuron diseases such as amyotrophic lateral sclerosis (ALS). In the spinal cord of MG-exposed and ALS mouse models, abnormalities have been mostly observed in the motor neurons. However, several recent studies have shown that exposure to MG and ALS also impacts the sensory systems. Yet, the role of sensory impairment in this degenerative process of exposure to MG and ALS remains unknown. In this study, we aimed at elucidating how the sensory system is affected by exposure to MG and ALS. To this end, we investigated the effects on gene expression of MG to control animals that remained under artificial gravity conditions and of the human superoxide dismutase 1 (SOD1) G93A mutation in a mouse model of ALS (SOD1G93A mice) in the mouse lumbar dorsal root ganglia (DRG). The overlap of genes with negatively correlated expression was greater than those with positively correlated expression between the DRG of MG-exposed and SOD1G93A mice. Additionally, genes related to Imoonglia (characteristics of both immune and glial cells) and macrophage increased in response to MG exposure, while satellite glial cell genes were expressed in response to SOD1 mutation. Next, we examined genes related to sensory neuron subtypes in the DRG. We found altered gene expression in genes related to proprioceptive and mechanoreceptive neurons in the DRG of MG-exposed and SOD1G93A mice. Remarkably, the expression of Atf3 and genes related to nociceptive neurons in the DRG of SOD1G93A mice at postnatal day (P) 120 was considerably altered, whereas MG-exposed and SOD1G93A mice at P30 presented little changes. These results indicate that exposure to MG and ALS affect gene expression in genes related to neurons and non-neuronal cells in the DRG, with significant differences between the effects of MG and the SOD1 mutation. Elucidation of the impact of exposure to MG and ALS pathogenesis in the DRG, including identification of the molecular pathways that regulate DRG dysfunction, will help better understand the differences in vulnerability and the triggering processes of impaired motor function associated with MG and ALS.